Analisis Kemampuan Pemecahan Masalah Matematika Berdasarkan Langkah Polya pada Materi SPLDV Siswa Kelas X SMK Negeri 1 Wewewa Barat (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to describe students' mathematical problem-solving abilities based on Polya's steps in the Two-Variable Linear Equation System (SLS) material in class X of SMK Negeri 1 Wewewa Barat. The study used a qualitative descriptive approach with data collection techniques in the form of tests, interviews, and documentation. The research instruments consisted of problem-solving ability test questions and interview guidelines arranged based on Polya's stages, namely understanding the problem, making a plan, implementing the plan, and re-checking. Data were analyzed using the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. The results showed that 31% of students were in the high category, 24% in the medium category, and 45% in the low category. Students in the high category were able to apply Polya's steps systematically, while students in the medium and low categories still had difficulties in understanding the problem, determining the solution strategy, and re-checking the answers obtained. The research findings showed that students' main weaknesses lie in the stages of understanding the problem and making a solution plan. The results of this study provide information for teachers in designing more effective learning to improve students' mathematical problem-solving abilities in the SLS material.